PERENCANAAN KEBUTUHAN MATERIAL PADA PROYEK PEMBANGUNAN DERMAGA DENGAN MENGGUNAKAN MATERIAL REQUIREMENT PLANNING (MRP) - Gunandar Syofrial (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
In each project activity management are usually applied that focus on aspects of planning, implementation, and supervision. So that project activities can run smoothly and finish well, there needs to be a plan and control, not only in managerial aspects but also in the engineering structure. Companies engaged in project contracting services can be said to be successful if they can use their time and project costs efficiently and effectively, so that every project confronted can be completed in a timely manner and in accordance with what was planned. In the dock construction project in this study requires a workforce of 24608 hours. And by using Material Requirement Planning (MRP) for material procurement, a schedule or order plan can be produced from the material that arrives on time that has been determined so that project implementation can proceed smoothly according to plan. Keywords: dock construction project, Material requirement Planning, material procurement